Aplikasi Pembalajaran Struktur Data Dengan Index Model Splay Tree Dengan Menggunakan Metode Binary Search Treeeac - Sony Bahagia Sinaga (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2020)
Index is a method used to test the process of retrieving data records in the process of searching for records that are commonly used in databases. Making an index simulation using the splay tree algorithm is done by entering the numbers that are used as indexes, the numbers entered by the user will be processed by the system to determine the index position in the simulation. A splay tree is a binary search tree adapting itself with additional properties that new elements are accessed quickly to access again. The application of tree theory is very useful in the study of data structures where tree theory will get an alternative data storage structure that is relatively better and more efficient. All normal operations in a binary search tree are combined with one basic operation, called splaying. Splaying the tree for a specific element composes the tree so that the elements are placed at the root of the tree. One way of doing this is to first perform a standard binary tree search for the element in question, and then use tree rotation specifically to bring the element up.